The human factor in the art of gynecology - Hernández-Yépez, Palmer J. (2019)
Mr. Editor. It is expected that the vast majority of published articles deepen the importance of quality of care by health personnel in the gynecological environment through the innovation of new techniques, care and management to follow. In this way the gynecological practice is enriched to establish a safe environment in patient care.